Applied positive pedagogy in sport coaching : international cases - Light, Richard, 1951-; Harvey, Stephen; Curry, Christina; Gibson, Kass; Hill, Nick; Jarrett, Kendall; Kuklick, Clayton; Paterson, Juliet; Pill, Shane; Pimenta, Ricardo; Price, Letitia; Razak, Mohammad Shah; et al. (New York : Routledge, Taylor & Francis Group, 2021)
"Positive Pedagogy is an athlete centred, inquiry based approach that transforms the way we understand learning and coaching in sport that can be successfully employed across a range of different sports and levels of performance. Applied Positive Pedagogy in Sports Coaching: International Cases reflects the uptake of it by coaches across different countries and sport settings through its complete focus on their experiences of using it and adapting it to their needs and contexts. Comprising of seventeen detailed chapters that examine both Team Sports (part one) and Individual Sports (part two), This book seeks to provide insight into the opportunities and challenges involved in the application of Positive Pedagogy for sport coaching (PPed). Critically, it also identifies any problems they encountered, how they addressed them and what they learned from these experiences. Acting as complementary text to the successful Positive Pedagogy for Sport Coaching second edition, Applied Positive Pedagogy in Sports Coaching: International Cases is an exciting, applied text that will be of vital reading for all practising sports coaches or physical education teachers looking to improve or even transform their professional practice as well as sports coaching students and researchers"--
Chapter 1:Providing a positive experience of learning: An Australian football (AFL) experience / Shane Pill Chapter 2: Positive Pedagogy in cricket coaching:A season of reflections / Kendall Jarrett and Elliot Wilson with Andy Siddall Chapter 3: Applying positive pedagogy to a season of basketball / Ricardo Pimenta Chapter 4: Coaching baseball with Positive Pedagogy / Clayton Kuklick Chapter 5. Football in a Japanese women's university / Richard Light Chapter 6. Enhancing enjoyment through positive pedagogy, wearable technology and flow / Michael Sup Chapter 7. Providing positive experiences of learning in girls' soccer (football) / Christina Curry Chapter 8. Using Positive Pedagogy in striking and fielding games/ Nick Hill Chapter 9. The Influence of a PPED Course on Coaching Practice / Richard Light and Mohammad Shah Razak Chapter 10. Swimming: Second kick in butterfly / Richard Light Chapter 11. Performing in chaos: Coaching transition for young triathletes using Positive Pedagogy / Juliet Paterson and Kass Gibson Chapter 12. Teaching javelin in a Singaporean school / Richard Light Chapter 13. Teaching for motivation and awareness in children's and youth gymnastics / Bianca Couto de Aguiar Chapter 14. Boxing technique / Richard Light Chapter 15. Positive Pedagogy for Strength and Conditioning in women's soccer / Letitia Price Chapter 16. Beach sprint starts / Richard Light Chapter 17. Teaching climbing techniques in Singapore / Mohammad Shah Razak.
OCLC-licensed vendor bibliographic record.
Keywords: Coaching (Athletics); Coaching (Athletics) -- Psychological aspects; Athletes -- Psychology